Thermodynamics of The Mixture of A Liquid Crystal and A Copolymer of Dimethylsiloxane - Coskun, Selin; Eran, B. Bilgin; Cankurtaran, O.; Karaman, F. (VIRTUAL INST PHYSICS, 2009)
5-dodecyloxy-2-[[[4-(S)-(2-methylbutoxy) phenyl] imino] methyl] phenol (BPIP) which represents liquid crystal transitions was synthesized by means of condensation reaction. On investigation by optical microscope, it was observed that BPIP maintained its chiral smectic mesophase of the fingerprint texture in its binary mixture with poly(methylhydrosiloxane-codimethylsiloxane) (HMS) in composition of 50% by weight. Liquid crystal-polymer interaction parameters of BPIP and HMS in the mixture were determined at temperatures between 90 and 105 in degrees C using trace amount solvents used as probes by inverse gas chromatography technique. The obtained small positive values of the liquid crystal-polymer interaction parameters being independent on solvent suggested that BPIP and HMS were immiscible but could not phase separate at studied temperature range.
Keywords: Chromatography; Thermodynamics; Miscibility; Mixture; Liquid Crystal; Poly(methylhydro siloxane-co-dimethylsiloxane); Materials Science